PENGEMBANGAN OLAHRAGA BELA DIRI PRAKTIS UNTUK MENCEGAH DAN MENGANTISIPASI ANCAMAN FISIK BAGI WANITA - Muhammad Syaleh; Ramadan (Jurnal Penjaskesrek, 2018)
Practical self-defense is a sport that utilizes the motion of muscles, brain and conscience in a realistic and rational way. Practical self-defense is obtained through the exercise of movement of all body members to apply 5 (five) elements of moral power, namely: strength, speed, accuracy, courage, and tenacity. Practical martial arts that are applied as self-protection for women of young adult age (15-20 years of age) from crime disorders. Self-defense began to be applied to students in schools as a basis for establishing physical resilience. The development of practical martial arts is carried out through the stages of analysis, design, development and implementation, as well as evaluation. The result of development is a pattern of gestures when receiving an attack or a crime occurs. The pattern of motion consists of 5 sets of martial arts movements based on received threats. Practical self-defense is obtained through small group testing, large group testing, group discussion (FGD) and expert testing using instruments such as questionnaires, interviews, and observations. The development of practical martial arts to prevent and anticipate physical threats for women is done by producing products in the form of practical martial arts for young adults (15-20 years of age). The results of the development of this research are: 1) Development of practical martial arts to prevent and anticipate physical threats for women can improve the skills of young adult women in the field of sports, 2) Through the development of practical martial arts this can provide the maturity of martial women young adults to prevent and anticipate if a physical threat occurs. Abstrak Bela diri praktis merupakan olahraga yang memanfaatkan senyawa gerak otot, otak serta nurani secara realistis dan rasional. Bela diri praktis diperoleh melalui latihan gerakan seluruh anggota tubuh untuk menerapkan 5 (lima) unsur daya moral yaitu : kekuatan, kecepatan, ketepatan, keberanian, dan keuletan. Seni bela diri praktis yang diterapkan sebagai perlindungan diri bagi wanita kelompok usia dewasa muda (usia 15-20 tahun) dari gangguan kejahatan. Bela diri mulai diterapkan pada siswa di sekolah-sekolah sebagai dasar pembentukan ketahanan fisik. Pengembangan bela diri praktis dilakukan melalui tahap analisis, desain, pengembangan dan implementasi, serta eavaluasi. Hasil pengembangan adalah pola gerak tubuh saat menerima serangan atau terjadi kejahatan. Pola gerak terdiri dari 5 rangkaian gerak bela diri berdasarkan ancaman yang diterima. Bela diri praktis diperoleh melalui uji kelompok kecil, uji kelompok besar, forum group discussion (FGD) dan uji pakar dengan menggunakan instrument berupa angket, wawancara, dan pengamatan. Pengembangan olahraga bela diri praktis untuk mencegah dan mengantisipasi ancaman fisik bagi wanita dilakukan dengan menghasilkan produk berupa gerakan bela diri praktis wanita kelompok usia dewasa muda (usia 15-20 tahun). Hasil pengembangan penelitian ini adalah: 1) Pengembangan bela diri praktis untuk pencegahan dan mengantisipasi ancaman fisik bagi wanita dapat meningkatkan kemampuan keterampilan wanita usia dewasa muda dalam bidang olahraga, 2) Melalui pengembangan olahraga bela diri praktis ini dapat memberikan kemapanan bela diri wanita usia dewasa muda untuk mencegah dan mengantisipasi jika terjadi ancaman fisik. Kata Kunci: Pengembangan, bela diri, praktis